Amos - Kessler, Rainer (W. Kohlhammer GmbH, 2021)
This commentary interprets the book of Amos as handed down in the Hebrew Bible: as a collection of the words of a prophet who emerges in the eighth century BCE and proclaims the end of the kingdom of Israel due to the social and ritual transgressions of its upper class, but in the end announces a safe future in abundant prosperity for survivors of the catastrophe from Judah and Israel. Diachronic analysis traces a path from the message of the eponymous prophet, which is recognizable only in outline, through the adaptations made by the first transmitters of the text following the end of the northern kingdom of Israel, to the final figure, who probably dates from the Persian era. Texts witnessing to the reception of the book & from other Old Testament writings to the present day & presented in highlights. Der Kommentar legt das Amos-Buch so aus, wie es in der Hebräischen Bibel überliefert ist: als Sammlung der Worte eines Propheten, der im 8. Jahrhundert v. Chr. auftritt, dem Königreich Israel wegen der sozialen und kultischen Vergehen seiner Oberschicht das Ende ansagt, am Schluss aber den Überlebenden der Katastrophe aus Juda und Israel eine sichere Zukunft in überbordendem Wohlstand ankündigt. Die diachrone Analyse zeichnet den Weg von der nur noch in Umrissen erkennbaren Botschaft des namengebenden Propheten über die Bearbeitungen seiner ersten Tradenten nach dem Ende des Nordreichs Israel bis zur Letztgestalt, die wohl aus der persischen Epoche stammt, nach. Schlaglichtartig werden Rezeptionen des Buches von anderen alttestamentlichen Schriften an bis in die Gegenwart beleuchtet